A Prior Magazine 23 / 23 Skidoo. - Roelandt, Els; Miller, Daniel; Knox, Bitsy; Menick, John; Gruijthuijsen, Krist; Rehberg, Vivian, Sky; Lesage, Dieter; Haq, Nav; Senior, David; Muller, Nat; Abu ElDahab, Mai; Janssen, Renske; et al. (Brussel : vzw Mark (A Prior Magazine), 2012)
thema nummer over Documenta (13) en Tino Sehgal
Daems, Anne ; Mroczek, Kenneth Andrew ; Delmotte, Monsieur ; Scanlan, Joe ; Garcia, Dora ; Hanssen, Karin ; Kriemann, Suzanne ; Ögüt, Ahmet ; Augustijnen, Sven ; Zins Brown, Andros ; Baers, Michael ; Martens, Renzo
boek